Insoluble anode for electroplating capable of reducing consumption of electroplating solution additives and preparation method thereof
By forming mesoporous titanium dioxide and iridium tantalum electrocatalytic layers on the surface of the electroplating insoluble anode and setting up a high resistance superhydrophobic nanosilica barrier coating, the problem of large additive consumption of electroplating solution is solved, and the effect of significantly reducing additive consumption and reducing environmental pollution is achieved.
Patent Information
- Application Number
- CN202110129931.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-01-29
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-01-29
AI Technical Summary
In the existing electroplating process, the electroplating solution additives consume a lot, resulting in high costs and serious environmental pollution, so methods to reduce additive consumption need to be sought.
An electroplated insoluble anode with an insoluble anode coating including a titanium matrix and a titanium matrix surface is used to form a mesoporous titanium dioxide and iridium tantalum electrocatalytic layer on the anode surface and a high resistance superhydrophobic nanosilicon dioxide barrier coating is provided on its surface to reduce the occurrence area of anodic oxidation reaction.
By reducing the area of the anodic oxidation reaction, the oxidation and degradation opportunities of electroplating solution additives are reduced, the consumption of electroplating solution additives is significantly reduced, and the cost and environmental pollution are reduced.
Smart Images

Figure CN112941605B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electroplating, and in particular to an electroplating insoluble anode capable of reducing consumption of electroplating solution additives and a preparation method thereof. Background Art
[0002] Circuit boards have evolved from single-layer to double-sided, multi-layer and flexible, and they still maintain their respective development trends. As they continue to develop towards high precision, high density and high reliability, they continue to reduce size, reduce costs and improve performance, making circuit boards still maintain strong vitality in the development of future electronic equipment.
[0003] Electroplating is very important in the entire circuit board manufacturing process, and it is related to the uniformity of the circuit boards and the uniformity of the vias.
[0004] Sting additive refers to a general term for a variety of chemical substances that need to be added to the plating solution in order to improve the quality of the coating during the electroplating process. Most of the electroplating additives are organic compounds, which can be divided into complexing agents, brighteners and auxiliary brighteners, leveling agents, pinhole removers, dispersants, wetting agents, smoke suppressants, etc. according to their functions in the electroplating solution.
[0005] During long-term and repeated use, the additives in the electroplating solution will be consumed in large quantities, and the electroplating solution needs to be replaced or the additives need to be added. The amount of additives added needs to be accurately detected to ensure the continuity of the electroplating before and after, so as to ensure the stability of the electroplating. The cost of replacing the electroplating solution and its environmental unfriendliness have led to an urgent need to improve the addition of electroplating solution additives. Summary of the invention
[0006] The purpose of the embodiment of the technical solution is to provide an insoluble anode for electroplating and a preparation method thereof, which can significantly reduce the consumption of additives in the electroplating solution.
[0007] The present invention provides an insoluble anode for electroplating which can reduce the consumption of electroplating solution additives. The anode comprises a titanium substrate and an insoluble anode coating on the surface of the titanium substrate, wherein mesoporous titanium dioxide is formed between the titanium substrate and the insoluble anode coating; a discontinuous barrier coating which occupies a larger area and has a higher resistance than that of the insoluble anode coating is provided on the surface of the insoluble anode coating, and a bare insoluble anode coating is provided between the discontinuous barrier coatings, and the bare insoluble anode coating occupies a smaller area than that of the barrier coating.
[0008] Furthermore, the material of the barrier coating is super-hydrophobic nano-silicon dioxide, and the insoluble anode coating is an iridium-tantalum electrocatalytic layer.
[0009] Furthermore, the barrier coating is super hydrophobic nano-silica.
[0010] Furthermore, the surface of the insoluble anode coating is rough.
[0011] Furthermore, the exposed insoluble anode coating is interspersed between the barrier coatings in the form of gap bands.
[0012] The present invention also provides a method for preparing an electroplating insoluble anode capable of reducing the consumption of electroplating solution additives, which comprises the following steps:
[0013] Growing mesoporous titanium dioxide on the surface of a titanium substrate;
[0014] Forming an insoluble anode coating on the surface of mesoporous titanium dioxide;
[0015] A barrier coating with a relatively large resistance is formed on the insoluble anode coating, and baking and sintering are performed to crack the barrier coating so that the area of the exposed insoluble anode coating is reduced.
[0016] Further, wherein, growing mesoporous titanium dioxide on the surface of a titanium substrate comprises the following steps;
[0017] Prepare titanium sol, wherein the titanium solution is a solution having a weight ratio of isopropyl titanate: P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer): acetylacetone: water: isopropanol = 0.9-1.1: 0.025-0.035: 0.4-0.6-: 0.9-1.1: 30-40, stir and mix, and age at a constant temperature in a container;
[0018] The titanium substrate after surface cleaning is dipped into the titanium sol by the pulling method. The dipped titanium substrate is dried for 24 hours in an environment with a humidity of 60% and a temperature of 20°C, and then calcined at 400°C for 4 hours with a heating rate of 5°C / min, and naturally cooled to form mesoporous titanium dioxide.
[0019] Furthermore, the insoluble anode coating is an iridium-tantalum electrocatalytic coating, and the preparation method of the iridium-tantalum electrocatalytic coating includes mixing 24-26 parts of chloroiridic acid, 28-32 parts of pentamethoxytantalum, 33-37 parts of hydrochloric acid, and 9-11 parts of isopropanol, and coating the mixed solution on a titanium substrate having mesoporous titanium dioxide several times, and sintering is performed after each coating, and finally cooling to room temperature.
[0020] Furthermore, the barrier coating is super hydrophobic nano-silica.
[0021] Furthermore, the preparation method of the barrier coating is: dip-coating the prepared iridium-tantalum electrocatalytic coating substrate in the super-hydrophobic nano-silica coating by the pulling method and drying the substrate at room temperature, dipping and pulling again after the sol gel, repeating the above operation three times, and drying and sintering.
[0022] The insoluble anode for electroplating that can reduce the consumption of electroplating solution additives provided by the technical solution of the present invention is provided with a barrier coating with a larger area. During the reaction, no anodic oxidation reaction occurs in the barrier coating area, that is, the electroplating additives are not oxidized and degraded in the barrier coating with a larger area. At the same time, since the exposed insoluble anode coating occupies a smaller area, and the oxidation reaction of the anode occurs in the low-resistance area, the current density of the exposed insoluble anode coating is high, and the bubbles generated by the exposed insoluble anode coating are large and quickly escape from the surface of the electroplating solution. These large bubbles stay in the electroplating solution for a very short time, thereby greatly reducing the chances of oxidative degradation of the additives in the electroplating solution. Therefore, the consumption of additives in the electroplating solution will be greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solution of the present technical solution, the drawings required for use in the implementation mode will be briefly introduced below. Obviously, the drawings described below are only some implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 It is a surface structure diagram of an insoluble anode for electroplating that can reduce consumption of electroplating solution additives provided by an embodiment of the present invention.
[0025] Figure 2 It is a partial cross-sectional schematic diagram of an insoluble anode for electroplating that can reduce the consumption of electroplating solution additives provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the technical solution to clearly and completely describe the technical solution in the embodiments of the technical solution. Obviously, the described embodiments are only part of the embodiments of the technical solution, not all of the embodiments. Based on the embodiments in the technical solution, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] See also Figure 1 and Figure 2 , an electroplating insoluble anode capable of reducing the consumption of electroplating solution additives, comprising a titanium substrate 100 and an insoluble anode coating 40 on the surface of the titanium substrate 100. Mesoporous titanium dioxide 30 is formed between the titanium substrate 100 and the insoluble anode coating 40. A barrier coating 20 having a larger area and a greater resistance than that of the insoluble anode coating is provided on the surface of the insoluble anode coating 40, so that the area occupied by the exposed insoluble anode coating 10 is smaller. That is, the exposed insoluble anode coating 10 is formed by the gaps of the barrier coating 20.
[0028] In this embodiment, the material of the barrier coating 20 is super-hydrophobic nano-silicon dioxide, and the insoluble anode coating 10 is an iridium-tantalum electrocatalytic layer. The high-resistance super-hydrophobic nano-silicon dioxide region occupies most of the area, and no anodic oxidation reaction occurs in this area. In addition, the iridium-tantalum oxide in the iridium-tantalum electrocatalytic layer enters the gap of the mesoporous titanium dioxide, increasing the specific surface area, thereby greatly enhancing the oxygen evolution activity.
[0029] The barrier coating 20 is formed by coating the barrier coating material on the surface of the insoluble anode coating and then baking and shrinking it.
[0030] The insoluble anode coating 10 has a rough surface. The insoluble anode coating with a rough surface can greatly enhance the surface bonding force between the barrier coating and the insoluble anode.
[0031] The exposed insoluble anode coating is interspersed between the barrier coatings in the form of gap bands. During the electroplating process, anodic oxidation occurs in the low-resistance area, and the surface of the low-resistance area is in the form of gaps. Since these gaps occupy a very small part of the entire anode surface, and the entire anode apparent current is generated in the gap band, the current density of the exposed insoluble anode coating in the form of gap bands is high, and the bubbles generated by anodic oxidation are large and quickly escape from the surface of the electroplating solution. These large bubbles stay in the electroplating solution for a very short time, thereby greatly reducing the chance of oxidative degradation of additives in the electroplating solution.
[0032] The following further describes a method for preparing an electroplating anode that can reduce the consumption of electroplating solution additives in combination with a plurality of embodiments.
[0033] Embodiment 1
[0034] S100, growing mesoporous titanium dioxide on the surface of a titanium substrate.
[0035] 1. Prepare titanium sol: specifically isopropyl titanate: P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer): acetylacetone: water: isopropanol = 1:0.03:0.5:1:36, the above units are parts by weight, after mixing, stir vigorously for 5 hours, and age at a constant temperature in a container at 50 degrees Celsius for 6 days.
[0036] 2. Use the pulling method to dip the cleaned titanium substrate (plate or grid) in the titanium sol, with a pulling rate of 12 cm / min. The dipped titanium substrate is dried for 24 hours in an environment with a humidity of 60% and a temperature of 20°C, then calcined at 400°C for 4 hours, with a heating rate of 5°C / min, and cooled naturally. After calcination, mesoporous titanium dioxide with good bonding with the titanium substrate is formed, with a specific surface area of 124m 2 / g, with an average pore size of 6.6 nanometers, making it an excellent carrier for iridium-tantalum catalytic coating.
[0037] S200, forming an insoluble anode coating on the surface of mesoporous titanium dioxide.
[0038] 25 parts of chloroiridic acid, 30 parts of pentamethoxytantalum, 35 parts of hydrochloric acid with a concentration of 1 mol / L, and 10 parts of isopropanol are coated on a titanium substrate with mesoporous titanium dioxide 10 times, and each coating is sintered at 500°C and finally cooled to room temperature to form an iridium-tantalum electrocatalytic coating with good electrocatalytic performance.
[0039] In this step, iridium tantalum oxide enters into the gaps of mesoporous titanium dioxide, increasing the specific surface area, thereby greatly enhancing the oxygen evolution activity.
[0040] S300, forming a barrier coating with a relatively large resistance on the insoluble anode coating, and baking and sintering are performed to crack the barrier coating so that the exposed insoluble anode coating has a smaller area.
[0041] The prepared iridium-tantalum electrocatalytic coating substrate was dipped in the super-hydrophobic nano-silica coating by the pulling method at a pulling speed of 14 cm / min. The substrate was dried at room temperature for 8 minutes, and then dipped and pulled again after the sol gelled. The above operation was repeated three times to obtain a 20-micron thick film, which was then dried at 80°C for 60 minutes and finally sintered at 400°C for 30 minutes. The sintering process volatilized the organic matter to form an acid-resistant super-hydrophobic nano-silica film with good bonding strength.
[0042] Embodiment 2
[0043] S100, growing mesoporous titanium dioxide on the surface of a titanium substrate.
[0044] 1. Prepare titanium sol: specifically isopropyl titanate: P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer): acetylacetone: water: isopropanol = 0.9: 0.035: 0.4: 1.1: 36, the above units are parts by weight, after mixing, vigorously stir for 5 hours, and age at a constant temperature in a container at 50 degrees Celsius for 6 days.
[0045] 2. Use the pulling method to dip-coat the titanium sol and clean the surface to obtain a titanium substrate (plate or grid shape), with a pulling rate of 12 cm / min. The titanium substrate after dipping is dried in an environment with a humidity of 60% and a temperature of 20°C for 24 hours, and then calcined at 400°C for 4 hours with a heating rate of 5°C / min, and cooled naturally. After calcination, mesoporous titanium dioxide with good bonding with the titanium substrate is formed, and its specific surface area reaches 124m 2 / g, with an average pore size of 6.6 nanometers, making it an excellent carrier for iridium-tantalum catalytic coating.
[0046] S200, forming an insoluble anode coating on the surface of mesoporous titanium dioxide.
[0047] 24 parts of chloroiridic acid, 32 parts of pentamethoxytantalum, 37 parts of hydrochloric acid with a concentration of 1 mol / L, and 9 parts of isopropanol are coated on a titanium substrate with mesoporous titanium dioxide 10 times, and sintered at 500°C after each coating, and finally cooled to room temperature to form an iridium tantalum electrocatalytic coating with good electrocatalytic performance.
[0048] S300, forming a barrier coating with a relatively large resistance on the insoluble anode coating, and baking and sintering are performed to crack the barrier coating so that the exposed insoluble anode coating has a smaller area.
[0049] The prepared iridium-tantalum electrocatalytic coating substrate was dipped in the super-hydrophobic nano-silica coating by the pulling method at a pulling speed of 14 cm / min. The substrate was dried at room temperature for 8 minutes, and then dipped and pulled again after the sol gelled. The above operation was repeated three times to obtain a 20-micron thick film, which was then dried at 80°C for 60 minutes and finally sintered at 400°C for 30 minutes. The sintering process volatilized the organic matter to form an acid-resistant super-hydrophobic nano-silica film with good bonding strength.
[0050] Embodiment 3
[0051] S100, growing mesoporous titanium dioxide on the surface of a titanium substrate.
[0052] 1. Prepare titanium sol: specifically isopropyl titanate: P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer): acetylacetone: water: isopropanol = 1.1: 0.025: 0.6: 0.9: 30, the above units are parts by weight, after mixing, vigorously stir for 5 hours, and age at a constant temperature in a container at 50 degrees Celsius for 6 days.
[0053] 2. Use the pulling method to dip-coat the titanium sol and clean the surface to obtain a titanium substrate (plate or grid shape), with a pulling rate of 12 cm / min. The titanium substrate after dipping is dried in an environment with a humidity of 60% and a temperature of 20°C for 24 hours, and then calcined at 400°C for 4 hours with a heating rate of 5°C / min, and cooled naturally. After calcination, mesoporous titanium dioxide with good bonding with the titanium substrate is formed, and its specific surface area reaches 124m 2 / g, with an average pore size of 6.6 nanometers, making it an excellent carrier for iridium-tantalum catalytic coating.
[0054] S200, forming an insoluble anodic coating on the surface of mesoporous titanium dioxide
[0055] 24 parts of chloroiridic acid, 28 parts of pentamethoxytantalum, 33 parts of hydrochloric acid with a concentration of 1 mol / L, and 10 parts of isopropanol are coated on a titanium substrate with mesoporous titanium dioxide 10 times, and each coating is sintered at 500°C and finally cooled to room temperature to form an iridium tantalum electrocatalytic coating with good electrocatalytic performance.
[0056] S300, forming a barrier coating with a relatively large resistance on the insoluble anode coating, and baking and sintering are performed to crack the barrier coating so that the exposed insoluble anode coating has a smaller area.
[0057] The prepared iridium-tantalum electrocatalytic coating substrate was dipped in the super-hydrophobic nano-silica coating by the pulling method at a pulling speed of 14 cm / min. The substrate was dried at room temperature for 8 minutes, and then dipped and pulled again after the sol gelled. The above operation was repeated three times to obtain a 20-micron thick film, which was then dried at 80°C for 60 minutes and finally sintered at 400°C for 30 minutes. The sintering process volatilized the organic matter to form an acid-resistant super-hydrophobic nano-silica film with good bonding strength.
[0058] Comparative Example
[0059] 1. Prepare titanium sol: specifically isopropyl titanate: P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer): acetylacetone: water: isopropanol = 1:0.03:0.5:1:36, the above units are parts by weight, after mixing, stir vigorously for 5 hours, and age at a constant temperature in a container at 50 degrees Celsius for 6 days.
[0060] 2. Use the pulling method to dip-coat the titanium sol and clean the surface to obtain a titanium substrate (plate or grid shape), with a pulling rate of 12 cm / min. The titanium substrate after dipping is dried for 24 hours in an environment with a humidity of 60% and a temperature of 20°C, and then calcined at 400 degrees Celsius for 4 hours with a heating rate of 5°C / min, and cooled naturally. After calcination, mesoporous titanium dioxide with good bonding with the titanium substrate is formed, with a specific surface area of 124m2 / g and an average pore size of 6.6 nanometers, becoming an excellent carrier for the iridium-tantalum catalytic coating.
[0061] 25 parts of chloroiridic acid, 30 parts of pentamethoxytantalum, 35 parts of hydrochloric acid with a concentration of 1 mol / L, and 10 parts of isopropanol are coated on a titanium substrate with mesoporous titanium dioxide 10 times, and each coating is sintered at 500°C and finally cooled to room temperature to form an iridium-tantalum electrocatalytic coating with good electrocatalytic performance.
[0062] Experimental data
[0063] Electroplating was performed in an electroplating solution, the main components of which included: 180 g / L sulfuric acid, 80 g / L copper sulfate, 60 mg / L chlorine, and an appropriate amount of electroplating additives. Electroplating was performed using the electroplating anodes prepared by the preparation methods of Example 1, Example 2, Example 3, and Comparative Example, and a phosphor copper soluble anode. The rate of consumption of the electroplating solution during the electroplating process is shown in the table below.
[0064] Table 1
[0065]
[0066] It can be seen from the above table that in the same electroplating solution, the phosphor copper soluble anode consumes the least amount of electroplating solution. However, due to the continuous consumption of the phosphor copper soluble anode during the electroplating process, the specific surface area changes continuously, resulting in uneven electric lines in the electroplating solution, which ultimately makes the quality of the electroplating layer unstable.
[0067] The surface of the insoluble anode coating of the comparative example does not have super-hydrophobic silica with gaps. Although the electroplating quality of the electroplating layer is stable, the consumption rate of the electroplating solution is very high.
[0068] As can be seen from the above table, the consumption rate of embodiments one, two and three is slightly greater than the consumption rate of the phosphor copper soluble anode, and is much lower than the consumption rate of the electroplating anode formed by the comparative example. Among them, the consumption rate of the electroplating anode formed by embodiment one and the stability of the quality of the electroplating layer are the best. Specifically, in the electroplating anode formed by embodiments one, two and three, anodic oxidation occurs in the low-resistance area during the electroplating process, and the surface of the low-resistance area presents a slit shape. Since these slits occupy a very small part of the entire anode surface, and the entire anode apparent current is generated in the slit band, the current density of the exposed insoluble anode coating in the slit band is high, and the bubbles generated by anodic oxidation are large and quickly escape from the surface of the electroplating solution. These large bubbles stay in the electroplating solution for a very short time, thereby greatly reducing the chance of oxidative degradation of the additives in the electroplating solution.
[0069] In summary, the insoluble anode for electroplating that can reduce the consumption of electroplating solution additives provided by the technical solution of the present invention is provided with a barrier coating with a larger area, and no anodic oxidation reaction occurs in the barrier coating area during the reaction, that is, the electroplating additives are not oxidized and degraded in the barrier coating with a larger area. At the same time, since the area occupied by the exposed insoluble anode coating is small, and the oxidation reaction of the anode occurs in the low-resistance area, the current density of the exposed insoluble anode coating is high, and the bubbles generated by the exposed insoluble anode coating are large and quickly escape from the surface of the electroplating solution. These large bubbles stay in the electroplating solution for a very short time, thereby greatly reducing the chances of oxidative degradation of the additives in the electroplating solution. Therefore, the consumption of additives in the electroplating solution will be greatly reduced.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an insoluble anode for electroplating that can reduce the consumption of electroplating solution additives, characterized in that: The electroplating insoluble anode capable of reducing the consumption of electroplating solution additives comprises a titanium substrate and an insoluble anode coating on the surface of the titanium substrate. Mesoporous titanium dioxide is formed between the titanium substrate and the insoluble anode coating; A discontinuous barrier coating having a larger area and a higher resistance than that of the insoluble anodic coating is provided on the surface of the insoluble anodic coating, and a bare insoluble anodic coating is provided between the discontinuous barrier coatings, and the bare insoluble anodic coating occupies a smaller area than that of the barrier coating; The surface of the insoluble anode coating is rough; The exposed insoluble anode coating is interspersed between the barrier coatings in the form of gap bands; The method comprises the following steps: Growing mesoporous titanium dioxide on the surface of a titanium substrate; Forming an insoluble anode coating on the surface of mesoporous titanium dioxide; A barrier coating with a relatively large resistance is formed on the insoluble anode coating, and baking and sintering are performed to crack the barrier coating so that the exposed insoluble anode coating area is reduced; Wherein, growing mesoporous titanium dioxide on the surface of a titanium substrate comprises the following steps: Prepare titanium sol, wherein the titanium solution is a solution having a weight ratio of isopropyl titanate: P123 (polyethylene oxide-polypropylene oxide polyethylene oxide triblock copolymer): acetylacetone: water: isopropanol = 0.9-1.1: 0.025-0.035: 0.4-0.6: 0.9-1.1: 30-40, stir and mix, and age at a constant temperature in a container; The titanium substrate after surface cleaning is dipped in titanium sol by a Czochralski method, the dipped titanium substrate is dried for 24 hours in an environment with a humidity of 60% and a temperature of 20°C, and then calcined at 400°C for 4 hours at a heating rate of 5°C / min, cooled naturally, and calcined to form mesoporous titanium dioxide; The insoluble anode coating is an iridium-tantalum electrocatalytic coating, and the preparation method of the iridium-tantalum electrocatalytic coating comprises mixing 24-26 parts of chloroiridic acid, 28-32 parts of pentamethoxytantalum, 33-37 parts of hydrochloric acid, and 9-11 parts of isopropanol, and coating the mixed solution on a titanium substrate having mesoporous titanium dioxide for several times, and sintering is performed after each coating, and finally cooling to room temperature; The barrier coating is super hydrophobic nano-silica.
2. The method for preparing an insoluble anode for electroplating that can reduce the consumption of electroplating solution additives according to claim 1, characterized in that: The preparation method of the barrier coating is: dip coating the prepared iridium tantalum electrocatalytic coating substrate in the super hydrophobic nano-silicon dioxide coating by the pulling method and drying the substrate at room temperature, dip coating and pulling again after the sol gel, repeat the above operation three times, and dry and sinter.
Citation Information
Patent Citations
Titanium-based composite anode as well as preparation method and application thereof
CN104593818A
Insoluble anode with improved structure
CN202323088U
Electroplating insoluble anode capable of reducing consumption of electroplating liquid additive
CN216304026U